An Investigation on the Effect of Extended Conjugation on the Photophysical Properties of Graphene Quantum Dot‐Porphyrin Dyads. Issue 43 (19th November 2021) - Pallikkara, Athira; Sebastian, Deepa; Ramakrishnan, Kala
Abstract: Noncovalent dyads embodied with porphyrin (PPy) and graphene quantum dots (GQDs) were subjected to photophysical studies with the aim of a deep understanding on the electron transfer dynamics in such systems. Peculiarities of a single fluorophore seems to be inadequate in light harvesting materials for various applications which can be rectified by the method of co‐sensitization. In this work Tetraphenylporphyrin (TPP) and Tetranaphthylporphyrin (TNaP) have been utilized for the preparation of the nanohybrid systems to realize the effect of conjugation on the photophysical properties of these materials. The photophysical studies of these nanohybrids such as UV‐Visible spectra, Fluorescence emission spectra and Time‐correlated single photon counting (TCSPC) were carried out. Both the ground and excited state interaction studies indicate an effective association between the two components in these nanohybrids. The photoexcited porphyrin molecules behave as electron donors and GQDs as acceptors and the interaction studies show that the quenching of the porphyrin derivatives occurs through a combined static and dynamic quenching mechanism in the PPy‐GQD nanocomposites. Moreover the extended conjugation in naphthyl system exalted the binding with quantum dots through π‐π interaction and results in augmented electron transfer than that in phenyl nanocomposite. The higher non‐radiative rate constant from TCSPC authenticates the above results. Understanding the photodynamics of electrons in such systems is significant for their effective utilization and practical applications of these materials in light harvesting devices and photocatalysis. Abstract : Non‐covalent dyads embodied with porphyrins and graphene quantum dots have been subjected to photophysical studies, with the aid of UV‐Visible absorption, fluorescence emission and TCSPC studies. Fluorescence emission spectrum and lifetime analysis shows a charge transfer mechanism which involves a combined static and dynamic quenching in its ground and excited states. Electron rich naphthyl groups with extended conjugation as compared to phenyl ring reinforces its alignment over the GQDs and that boosted the electron transfer dynamics in TNaP‐GQD nanohybrid.